ARTIFICIAL INTELLIGENCE FROM THE POSITION OF MIND SCHEME - Evgeniy V. Asaulenko (Открытое образование (Москва), 2016)
The paper touches upon the problem of «adaptive navigation». The article depicts an approach to its solution based on a particular topology – a square lattice. The decision is grounded on the modern comprehension of mechanisms of memory and thinking. Forgetting as a decreasing logarithmic function of time is considered. The concept of the mental scheme is introduced. The method of visualization of mental schemes is described. Particular examples of mind schemes are presented.